Perspektif Mahasiswa Pada Matakuliah Pendidikan Kepramukaan Di Program Studi PGSD Universitas Djuanda - Erlina Erlina; Helmia Tasti Adri (Pedir Research Institute, 2022)
Character education can be formed through scouting education lesson. One of the courses in the Elementar School Teacher Education Study Program FKIP UNIDA is the scouting education course. This study aims to determine the student’s perspective on the scouting education course at FKIP UNIDA. A Qualitative approach was used in this study. The research subjects were students of the Djuanda University Elementary School Teacher Education study program. Data collection was carried out using interview techniques and literature study. The result of this research is that there are some student who do not understand the material taught by the course. Student studyscouting only to fulfill the credits in lectures, so that character education they want to instill in accordance with the goalsof scouting does not reach student. But on the other hand there are some student who feel the importance of scouting education to form honest, responsible, disciplined, hard-working, confident, and independent characters..